Prediction of the efficacy of neoadjuvant chemoradiotherapy in patients with rectal cancer based on a texture analysis of T2-weighted magnetic resonance tumor image obtained at primary staging - Yana A. Dayneko; Tatiana P. Berezovskaya; Oleg A. Mirzeabasov; Sergey O. Starkov; Sofiya A. Myalina; Aleksey A. Nevolskikh; Sergey А. Ivanov; Andrey D. Kaprin (Digital Diagnostics)
BACKGROUND: Recently, significant efforts have been undertaken to find potential noninvasive biomarkers for predicting the response of locally advanced rectal cancer to neoadjuvant chemoradiotherapy.